2011
DOI: 10.1158/1055-9965.epi-10-0889
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Hepatitis B and C Viruses and Risk of Lymphoid Malignancies in the European Prospective Investigation into Cancer and Nutrition (EPIC)

Abstract: Background: Case-control studies suggested a moderate, but consistent, association of hepatitis C virus (HCV) infection with lymphoid tissue malignancies, especially non-Hodgkin lymphoma (NHL). More limited data suggested that hepatitis B virus (HBV) infection might also be associated with NHL. However, prospective studies on the topic are few.Methods: A nested case-control study was conducted in eight countries participating in the EPIC prospective study. Seven hundred thirty-nine incident cases of NHL, 238 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 39 publications
3
68
1
Order By: Relevance
“…We observed much lower levels of markers of liver damage compared with NHANES overall and particularly no increase in these markers in individuals with low glycated haemoglobin. Furthermore, the prevalence of seropositive hepatitis C assessed in a subset of the UK EPIC cohorts was 0.6% [28], which is also much lower than in NHANES participants (2.3%); this might therefore partly explain the divergent findings for the association between glycated haemoglobin and mortality risk.…”
Section: Discussionmentioning
confidence: 85%
“…We observed much lower levels of markers of liver damage compared with NHANES overall and particularly no increase in these markers in individuals with low glycated haemoglobin. Furthermore, the prevalence of seropositive hepatitis C assessed in a subset of the UK EPIC cohorts was 0.6% [28], which is also much lower than in NHANES participants (2.3%); this might therefore partly explain the divergent findings for the association between glycated haemoglobin and mortality risk.…”
Section: Discussionmentioning
confidence: 85%
“…lymphocytic leukemia (8)(9)(10)(11). Malignant transformation may occur directly via B cell infection and transformation, or indirectly via chronic Ag-driven stimulation of the B cell receptor (BCR) that has identical heavy and light chain specificity for secreted mc Ig.…”
Section: Introductionmentioning
confidence: 99%
“…They were compared with 2028 witnesses from the point of view of the presence of serological markers of hepatitis B and C viruses. The authors concluded that chronic HBV infection may be a risk factor for malignant lymphoid proliferations [66].…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%